Penggunaan assessment for learning (AFL) melalui peer assessment untuk meningkatkan mathematical problem solving - Dian Kurniawan (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2016)
The aim of the study to examine differences upgrade in mathematical problem solving of students in Calculus 1 Course after getting learning Assessment For Learning Through Peer Assessment. Two classes selected by cluster random sampling, the class I-C selected as an experimental class and class I-B as the control class. The study uses a method mix. Based on data analysis, by using assessment for learning through peer assessment, the students had the mathematical problem-solving abilities better than students who do not use it. Also based on the quality normalized gain, analysis represents the improvement of mathematical problem solving for students who receive peer learning through better assessment than students who did not get it. The students were able to conduct discussions properly, take feedback in questions, comments and objections for the teaching materials and worksheets and also were able to assess they friend tasking result properly through peer assessment.